Where do roots take up water? Neutron radiography of water flow into the roots of transpiring plants growing in soil - Zarebanadkouki, Mohsen; Kim, Yangmin X.; Carminati, Andrea (The New phytologist, 2013)
Where and how fast does water flow from soil into roots? The answer to this question requires direct and in situ measurement of local flow of water into roots of transpiring plants growing in soil. We used neutron radiography to trace the transport of deuterated water (D2O) in lupin (Lupinus albus) roots. Lupins were grown in aluminum containers (30 × 25 × 1 cm) filled with sandy soil. D2O was injected in different soil regions and its transport in soil and roots was monitored by neutron radiography. The transport of water into roots was then quantified using a convection–diffusion model of D2O transport into roots. The results showed that water uptake was not uniform along roots. Water uptake was higher in the upper soil layers than in the lower ones. Along an individual root, the radial flux was higher in the proximal segments than in the distal segments. In lupins, most of the water uptake occurred in lateral roots. The function of the taproot was to collect water from laterals and transport it to the shoot. This function is ensured by a low radial conductivity and a high axial conductivity. Lupin root architecture seems well designed to take up water from deep soil layers.